Glosy do ontologii spektaklu radiowego - Mucha, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The article focuses on inaccuracy of terms which has appeared in the radio drama literature. According to propounded thesis, original radio drama is a kind of adaptation, because its existence in proper auditory form always requires a specific intersemiotic translation which involves at least acoustic scenario fruition. The thesis was verified on the material of Drugi pokój – Zbigniew Herbert’s radio-play directed by Waldemar Modestowicz. Terms ‘original radio drama’ and ‘radio-play adaptation’ have the same basis, which demands analysis of radio drama’s features. ‘Subject’ and ‘recipient’ of an audio work focus on issues of perception, which is a starting point for deliberation.